2019
DOI: 10.1128/mra.00849-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of a Coxsackievirus A20 Strain Recovered from a Child with Acute Flaccid Paralysis in Nigeria

Abstract: In light of recurrent outbreaks of circulating vaccine-derived poliovirus 2 (cVDPV2) in Nigeria, we describe the genome sequence of a coxsackievirus A20 strain (CVA20).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Most cVDPVs detected to date have recombinant genomes typically composed of a P1 region (encoding capsid proteins) derived from parental OPV and P2–P3 regions (encoding non-structural proteins) derived from non-vaccine viruses, most likely NPEV-C strains ( Kew et al., 2005 ; Combelas et al., 2011 ). The NPEV-C sequences found in the P2–P3 regions of previously described pathogenic cVDPVs are CVA17, CVA20, CVA11, and CVA13 ( Rakoto-Andrianarivelo et al., 2007 ; Faleye et al., 2019 ). In our study, we similarly observed that strain SPA866 may be a vaccine/non-vaccine recombinant given that P2–P3 regions showed high divergences (18.8% and 17%, respectively) with Sabin 2, suggesting that the putative non-OPV sequence of SPA866 was derived from co-circulating NPEV-C.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most cVDPVs detected to date have recombinant genomes typically composed of a P1 region (encoding capsid proteins) derived from parental OPV and P2–P3 regions (encoding non-structural proteins) derived from non-vaccine viruses, most likely NPEV-C strains ( Kew et al., 2005 ; Combelas et al., 2011 ). The NPEV-C sequences found in the P2–P3 regions of previously described pathogenic cVDPVs are CVA17, CVA20, CVA11, and CVA13 ( Rakoto-Andrianarivelo et al., 2007 ; Faleye et al., 2019 ). In our study, we similarly observed that strain SPA866 may be a vaccine/non-vaccine recombinant given that P2–P3 regions showed high divergences (18.8% and 17%, respectively) with Sabin 2, suggesting that the putative non-OPV sequence of SPA866 was derived from co-circulating NPEV-C.…”
Section: Discussionmentioning
confidence: 93%
“…Future whole-genome sequencing of co-circulating human NPEV-C strains from West African countries, such as Senegal, Guinea, and Mauritania, will provide a clearer picture of the contribution of recombinants to the emergence of West African VDPVs. Vaccine/non-vaccine breakpoints in the genomes of recombinant VDPVs are usually located at the end of the 2A- or 2B-coding sequences, although they may also be found close to the vaccine/non-vaccine junction or in the P3 region ( Rakoto-Andrianarivelo et al., 2007 ; Bessaud et al., 2016 ; Faleye et al., 2019 ; Joffret et al., 2021 ). Here we show that the likely site of recombination of strain SPA866 is in the 2A region, which is in accordance with previous studies describing breakpoints in the genomes of recombinant VDPVs type-2 from Madagascar, Nigeria, and the Central African Republic located at this position ( Rakoto-Andrianarivelo et al., 2007 ; Faleye et al., 2019 ; Joffret et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%